Projects office and product development process: a case study in the plastic industrial sector (Revista Brasileira de Contabilidade e Gestão, 2021)
This study aimed to identify the participation of the projects office department in the product development process, in the context of a company in the plastics sector located in the north plateauregion of Santa Catarina. For this purpose, a qualitative research strategy was used, before an exploratory study procedure. The results were obtained through an interview script applied to the projects officeand a descriptive memorial from the insight of the organization's Engineering area. Among the conclusionsobtained, its continuous participation in all stages involved in this process stands out, aiming to improve and reduce the development time of a new product within the company. This feedback reflects the need for people and an adequate tool to assist in project management, an issue highlighted with relevance in the deliberations found.
Keywords: Product Development; Delivery of Value; Projects